Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Kinerja Guru Terhadap Prestasi Belajar Peserta Didik di SMP Kristen Palangka Raya - Juliarti Lbn. Gaol; Alexandro, Rinto; Merisa Oktaria; Kharisma Nugraha Putra (Edunomics Journal, 2024)
Students' learning achievement is a manifestation of the success of Palangka Raya Christian Junior High School, but in reality there are still many students who really excel but have not seen or even do not know their achievements. This study was conducted to determine the effect of the principal's leadership style and teacher performance on student learning achievement. This study uses quantitative research methods. The population of this study were students in grades VIII and IX of Palangka Raya Christian Junior High School with a sample size of 55 respondents. The data collection technique used a questionnaire which was arranged on a Likert scale of 1 to 4 and analyzed using multiple linear regression, t-test, f test and the coefficient of determination (R2) SPSS v22. The results showed that; (1) partially the principal's leadership style has a significant effect on student learning achievement. (2) partially teacher performance has a significant effect on student learning achievement. (3) simultaneously the principal's leadership style and teacher performance have a significant effect on student learning achievement with a contribution of 39.5% while the remaining 60.5% are other factors not identified in this study.